Seasonal Variability in the Microbial Plankton Community in a Semienclosed Bay Affected by Upwelling: The Role of a Nutrient Trap - Figueiras, Francisco G.; Teixeira, Isabel G.; Froján, María; Zúñiga, Diana; Arbones, Belén; Castro, Carmen G. (Frontiers in Marine Science, 2020)
The Ría de Vigo is a semienclosed bay in northwestern Iberia that is affected by seasonal upwelling (spring to autumn) that triggers high levels of primary productivity. Fisheries and aquaculture coexist with other human activities, such as shipbuilding and tourism, in this area. The microbial plankton community in this system was studied to understand how this community is structured and progresses seasonally. Autotrophic biomass (AB) dominated from spring to autumn when upwelling prevailed, while AB and heterotrophic biomass (HB) covaried throughout the year as HB:AB = 0.26 ± 0.04 (r2 = 0.7), indicating a link between the two communities. Diatoms and autotrophic nanoflagellates accounted for 80 ± 18% of the AB, whereas the HB was mainly composed of heterotrophic bacteria (36 ± 11%) and heterotrophic nanoflagellates (30 ± 12%). The AB and HB, as well as their main components, showed a continuous increase during the upwelling season that was attributed to growth. However, a sudden increase occurred in autumn, when downwelling caused the biomass to accumulate before leading to the low values in winter. As upwelling promotes the export of materials to the open ocean, the increase in biomass was possibly due to the existence of a nutrient trap that fueled phytoplankton growth through recycling at the sediment-water interface a substantial portion of the organic matter previously synthetized in the water column. The reorganization of the community that followed the winter decrease in biomass began with the proliferation of small plankton forms.